The extent of judicial review of administrative decision and orders of the industrial court- the effectiveness of the ouster clauses under The Trade Union Act 1959 (revised) 1981, and Industrial Relation Act 1967 / Mohd Amin Hasbollah - Hasbollah, Mohd Amin (Faculty of Law, 1987)
The system of delegated subordinate or subsidiary legislation has come in vogue in all democratic countries. One of the factors which contributed to the growth of delegated legislation in democratic countries is that modern country discharges multifarious functions, It also helps to discharge undue burden of the legislature and to economise the legislative time. Such a system introduces flexibility. As Wade and Phillips points out, subsidiary or delegated legislation fulfills the need of modern times "that something less cumbrous and more expeditios than an a Act of Parliment shall be available to amplify the main provisions, to meet the unforseen contingencies and to fascilitate adjustment that may be called for after the scheme has been put into operation."1 Therefore, such a system can be regarded as useful and indispensable technique of modern government.